Mining and quarrying in neolithic Europe : a social perpsective - Teather, Anne M.; Topping, Peter; Baczkowski, Jon (Neolithic Studies Group seminar papers, 2019)
"This book presents the proceedings of a seminar held in November 2017, organised by the Neolithic Studies Group (NSG), that forms part of an ongoing series of NSG seminar papers."--